Regional differences in land use affect population performance of the threatened insectivorous plant Drosophyllum lusitanicum (Droseraceae) (Diversity and Distributions, 2003)
We analyse populations of the insectivorous plant Drosophyllum lusitanicum (L.) Link (Droseraceae) and their habitats throughout the species’ distribution range (Portugal, Spain and Morocco), and examine their relations. We have surveyed 32 populations and we analyse their demographic structures, accompanying plant communities (by TWINSPAN analyses), and relationships between population features and several edaphic and nonedaphic environmental variables (by multiple regression analyses). Plant communities, their ﬂoristic richness and degree of endemism change across the geographical range of Drosophyllum. Populations vary strongly in size, density and age structure. Their recruitment seems largely determined by competition with the surrounding vegetation, while only weak relationships were detected between population performance and other environmental factors. The demographic structure of populations exhibits a marked geographical differentiation, with populations becoming older and sparser towards the north-western part of the range. The largest and presumably most stable populations are mostly found in southern Spanish heathlands, which are nowadays scarcely affected by man. Moroccan populations suffer from browsing by cattle and experience an accelerated generation turnover, while most Portuguese populations occur in afforested areas and experience strongly reduced recruitment. The historical distribution range of Drosophyllum within its peculiar habitat has probably been relatively stable, but recent regional differences in human land use have resulted in present-day differences in population performance, as well as in types and degrees of threat across the three countries involved. Conservation strategies should take into account this range-wide variation and combine approaches on different spatial scales.

Soil seed bank and floristic diversity in a forest-grassland mosaic in southern Spain (Journal of Vegetation Science, 2003)
Soil seed bank and floristic diversity were studied in a forest of Quercus suber, a forest of Quercus canariensis and a grassland, forming a vegetation mosaic in Los Alcornocales Natural Park, southern Spain. The soil seed bank was estimated by the germination technique. In each community patch, diversity, woody species cover and herbaceous species frequency was measured. Three biodiversity components – species richness, endemism and taxonomic singularity – were considered in the vegetation and the seed bank. Forest patches had a soil seed bank of ca. 11 200-14 100 seed.m–2 and their composition had low resemblance to (epigeal) vegetation. The grassland patch had a more dense seed bank (ca. 31 800 seed.m–2 ) and a higher index of similarity with vegetation, compared with the forests nearby. The complete forest diversity was 71-78 species on 0.1 ha, including 12-15 species found only in the seed bank; the grassland species richness was higher (113 species on 0.1 ha). We discuss the role of soil seed banks in the vegetation dynamics and in the complete plant biodiversity of the mosaic landscape studied.

Biodiversity of woody species in oak woodlands of southern Spain and northern Morocco (Forest Ecology and Management, 1999)
Three biodiversity parameters ± species richness, endemic species richness and taxonomic singularity ± have been evaluated for the woody understorey of oak woodlands on sandstone-derived substrates, on both sides of the Strait of Gibraltar. There is a similarity in ¯oristic composition and ecological distribution of woody plant communities across the Strait. Nevertheless, we have detected signi®cant differences. These include a general reduction in species richness, number of endemic species and taxonomic singularity (at the community level), and a greater abundance of widespread, generalist species, on the southern side (Moroccan) communities, as compared to the north (Spanish ones). We interpret these differences as partly caused by the contrasting management of woodlands, with higher slashing and browsing pressure in Morocco.

Patterns of ecological, chorological and taxonomic diversity at both sides of the Strait of Gibraltar (JOURNAL OF VEGETATION SCIENCE, 1996)
Diversity relations in Mediterranean heathlands and the understorey of oak woodlands on sandstone-derived substrates were studied at both sides of the Strait of Gibraltar. Trends in species composition and cover were analysed by Detrended Correspondence Analysis; the first axis, assumed to reflect a main environmental gradient, was used to analyse the patterns of three aspects of community diversity. Species richness, i.e. number of species along a 100-m transect, shows a humpbacked trend along the gradient, with the highest values in the understorey of evergreen Quercus suber woodlands, associated with soils of intermediate fertility and moisture status. The number of endemic species is highest in open heathlands, associated with more extreme conditions of acid, infertile soils on exposed ridges. The taxonomic singularity, as measured by the inverse of the average number of species per genus at each site, is highest at the most fertile and moist sites occupied by semideciduous Q. canariensis woodlands. A comparison between northern (Spanish) and southern (Moroccan) sides of the Strait of Gibraltar shows a general concordance of the trends of woody plant communities along the main environmental gradient. However, significant differences of the southern samples are: (1) lack of some differential, habitat-specific species and greater abundance of wide spread generalists; and (2) a general reduction in species diversity, number of endemics and taxonomic singularity. We interpret these differences as affected partly by the smaller extent and fragmentation of sandstone areas in the south, and partly by the higher impact of slashing and grazing there.

Biodiversity components and conservation of mediterranean healthlands in Southern Spain (Biological Conservation, 1995)
Biodiversity is a complex issue which has frequently been extremely simplified both by equating it with species richness, and by addressing it at the level of regional floras or faunas. In this paper we carry out a detailed assessment of biodiversity for conservation of Mediterranean heathlands and related woodland understoreys on acidic ‘islands’ in the Gibraltar Strait region which are remarkable for their high species richness, high endemism and low ratio of species per genus. The relationship between the cover of woody plant species and environmental variables was studied by multivariate (DCCA) analysis of 30 samples. Species richness shows a unimodal relationship along the main environmental gradient primarily determined by physiological tolerance to low pH and ecological competition. Quercus suber woodland understoreys under intermediate environmental conditions are highest in species richness. Woody plant species are assigned to one of seven types of geographic ranges, and distributional spectra of community samples are represented. Open heathlands on nutrient-poor soils on mountain ridges are highest in endemism. Species distinctness was estimated as the inverse of the average number of species per genus (‘taxonomic singularity’) within the Mediterranean Basin, Ibero-North African and Southwestern Spain ranges. Quercus canariensis woodland understoreys on more fertile soils on valley bottoms present the highest taxonomic singularity. The analysis at the community level of the three proposed biodiversity components (species richness, endemism richness and taxonomic singularity) is interpreted with the aim of formulating sound conservation strategies of the communities examined. Although we use communities in the Gibraltar Strait area as a particular case study, we suggest that this methodology would help conservation efforts in other areas.